Tuning of piezoelectric parameters in the phase transition process via the transient state - Ishchuk, V.M.; Spiridonov, N.A. (Functional Materials, 2008)
The influence of the electric field on the stability of phases in antiferroelectric substance with a small difference in energies of the ferroelectric (FE) and antiferroelectric (AFE) states is studied. It is theoretically predicted that the interaction between the coexisting domains of (FE) and (AFE) phases provides the stability of the inhomogeneous intermediate state of the substance in external electric field. The composition-electric field phase diagrams with intermediate state are obtained for the lanthanum modified lead zirconate-titanate based solid solutions. Variation of piezoelectric properties of these solid solutions during the phase transition via intermediate state is studied. The effective control of piezoelectric parameters is shown to be possible in materials with such phase transition.